The paradox of stability and change: a case study. Issue 1 (13th November 2019) - Lin, Haifen; Qu, Tingchen; Li, Li; Tian, Yihui
Abstract : Purpose: The traditional dualism view regards stability and change as opposites and separate, two essential but largely incompatible and mutually exclusive elements in an organization, and it advocates contingency theories to handle the paradox situation; more recent research has adopted the paradoxical lens to highlight both the contradiction and the interdependence between the two elements. This paper aims to address how an organization pursues stability and change simultaneously, i.e., how stability and change contradictorily enable each other to promote the development of an organization. Design/methodology/approach: By adopting a case study on the strategic and structural change of Signcomplex in China, this paper attempts to explore the paradoxical relationship between stability and change, especially their interdependence. Multiple approaches were used during data collection to meet the criteria for trustworthiness, and the data analysis went through a five-step process. Through this analysis, the main mechanisms of stability and change were identified. An analysis was also conducted on how these stable and variable mechanisms enable each other, and finally, a framework was set up to show this paradoxical relationship. Findings: The results confirm the paradox of stability and change: stability enables change by supplying security and consistency, offering reserved knowledge and skills and enabling commitment and the provision of resources for a better realization of the change. Change enables a firm to set up a new state of stability through variable mechanisms such as trial-and-error and exploration activities. The results also indicate that the nature of organizational change is to help an organization reach a new stable stage with higher efficiency and that organizational development relies on the paradoxical effects of both stability and change. Research limitations/implications: This research is constrained by several limitations. The findings need to be further confirmed through the investigation of more organizations; other stable mechanisms, such as habits, tight coupling, commitments, control and low variance, and variable mechanisms, such as search, mindfulness, redundancy and openness, should be considered. As an organization may experience many cross-level or cross-department changes which struggle with each other for resources and with stable mechanisms, to explore the paradox, future research may need to conduct a more in-depth examination of the system of change. Originality/value: The findings offer some valuable insights for further research and hold important implications for management practices, especially management practices in a Chinese context. The findings extend the existing paradox theory by further revealing how stability and change enable each other and offer a paradoxical perspective to look into the nature of organizational change and organizational development. The results remind managers to rethink the relationship between stability and change, to factor these coexisting concepts into their decision-making and to accept, understand and use this paradoxical relationship to realize synergistic effects for the firm.